2020
DOI: 10.17656/jzs.10794
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of Fasciola species in sheep and goats in Sulaymaniyah Province, Northern Iraq

Abstract: Both F. hepatica and F. gigantica are considered as the main causes of human and animal fascioliasis that have much medical and economic importance worldwide. Nowadays, identification and description of Fasciola species using molecular-based techniques are critical and reliable approach in most laboratories and research centers. Thus, this research aimed to investigate the prevalence of fascioliasis and molecular characterization of isolated Fasciola species in sheep and goats in Sulaimaniyah province, Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
2
6
2
Order By: Relevance
“…A study was done in Mazandaran, northern Iran, who they found that F. hepatica is more dominant in sheep than goats (22). The prevalence of F. hepatica in sheep in the present study was lower than those studies done in Sulaymaniyah Province, Abu-Ghraib district and Kirkuk province, which were 15%, 12.73% and 72% by using PCR, ELISA and sedimentation technique respectively (13,14,15). Although, the result of the present study was lower than those results proved in Iran, which were 32% by sedimentation technique (17).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…A study was done in Mazandaran, northern Iran, who they found that F. hepatica is more dominant in sheep than goats (22). The prevalence of F. hepatica in sheep in the present study was lower than those studies done in Sulaymaniyah Province, Abu-Ghraib district and Kirkuk province, which were 15%, 12.73% and 72% by using PCR, ELISA and sedimentation technique respectively (13,14,15). Although, the result of the present study was lower than those results proved in Iran, which were 32% by sedimentation technique (17).…”
Section: Resultscontrasting
confidence: 63%
“…The use of corticosteroid with flukicide give quickest and the best response to treatment of fasiollosis, This could be explained that the use of corticosteroid assisted the flukicide in preventing immune damage and fibroplasias inflicted by the liver flukes beside to improvement metabolic actions of the animal (12). In Iraq, the prevalence of F. hepatica in sheep and goats in Sulaymaniyah Province was 15% by using PCR (13), While in Abu-Ghraib district the prevalence of F. hepatica in local sheep was 12.73% by using ELISA (14), in other hand, in Kirkuk province, the prevalence of F. hepatica in sheep and goat was 72% and 11% by sedimentation technique respectively (15). In Turkey, the prevalence of F. hepatica in sheep was 7.50% by using ELISA (16).…”
Section: Introductionmentioning
confidence: 99%
“…The result agreed with (Kordshooli et al, 2017) in Iran, who detected that the prevalence rate of F. hepatica were 5.22% of sheep, 2.15% of goat, and 11.15% of cattle. Fasciola species are usually found in herbivores in various parts of Iraq (Hamoo et al, 2019, Raoof et al, 2020, Abdulwahed and Al-Amery, 2019. The observation could be a return to husbandry practices and climatic variation including rain and warmth which had significant effects on the remainder of both intermediate host and the larval stages (miracidium and cercariae) of the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…Serological findings do not differentiate between these species (Amor et al, 2011, Alajmi, 2019. Different molecular methods were employed in the analysis, taxonomy, and fasciola studies like complete genome sequencing and single nucleotide polymorphism (Moazeni et al, 2012, Raoof et al, 2020. The PCR amplification method improves many templates for initial priming that allow the primers to anneal the known conserved regions to amplify across unknown variable regions and better diagnose species (Eman et al, 2016, Mohammed et al, 2016, Hassan, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Diagram of ITS-1 and ITS-2 markers Raoof et al (2020). used the mitochondrial 28S rRNA gene in a molecular study and phylogenetic analysis for Fasciola species isolated from sheep and goats of Sulaymaniyah governorate.…”
mentioning
confidence: 99%